2015
DOI: 10.19184/jid.v15i2.813
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cinnamon (Cinnamomum burmanii) Aqueous Extract on Pancreas Structure of Diabetic Mice (Mus musculus) Strain Balb-C

Abstract: The objectives of this study were to observe effect and  the effective dose of cinnamon (Cinnamomum burmanii) aqueous extract on pancreas structure of strain Balb-C mice (Mus musculus) diabetic after alloxan exposure. A total of 30 strains Balb-C mice (Mus musculus L.) were divided into 5 groups. Negative control group was not induced  by alloxan and a positive control group was induced alloxan 0,15 mg/g bw intraperitoneally for 9 days. The treatment group was divided into 3 groups was induced alloxan 0,15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Research by Kusumaningtyas et al [7] by giving cinnamon powder steeping at a dose of 0.73 mg/g bw was able to improve the pancreatic structure of male mice with Balb-C Strain after being exposed to alloxan. The administration of lemongrass steeping at a dose of 3.6 ml/200grBB and 0.9 ml/200grBW rats showed that lemongrass stew was able to reduce blood glucose, triglyceride, LDL and total cholesterol levels, as well as increase HDL levels [4].…”
Section: Resultsmentioning
confidence: 97%
“…Research by Kusumaningtyas et al [7] by giving cinnamon powder steeping at a dose of 0.73 mg/g bw was able to improve the pancreatic structure of male mice with Balb-C Strain after being exposed to alloxan. The administration of lemongrass steeping at a dose of 3.6 ml/200grBB and 0.9 ml/200grBW rats showed that lemongrass stew was able to reduce blood glucose, triglyceride, LDL and total cholesterol levels, as well as increase HDL levels [4].…”
Section: Resultsmentioning
confidence: 97%
“…Cinnamaldehyde is able to ward off free radicals by giving hydrogen atoms to free radicals and converting them to a more stable form. (Kusumaningtyas et al, 2014). Cinnamon has also been shown to improve pancreatic cell function because in the pancreas there is an increase in beta cell proliferation and the formation of new pancreatic lobes for 8 weeks (Bonner-Weir et al, 2010).…”
Section: Figure 2 Graphic Results Of Testing Sugar Levels In Each Groupmentioning
confidence: 99%
“…Mursyida and Wati (2021) states that steeping cinnamon can act as an anti-diarrheal because the content of cinnamon can inhibit the growth of Escherichia coli. On the other hand, cinnamon is also very good at lowering blood sugar, this is evidenced by the research of Kusumaningtyas et al (2014) which states that test animals of mice experienced an improvement in the structure of the pancreas due to infusion of cinnamon with doses of 0.73 mg/g bb and 1.09. mg/g bw, this is thought to be due to the presence of antioxidant cinnamaldehyde in the brewing of cinnamon powder which is able to ward off free radicals due to alloxan exposure. In order to maximize the reduction in blood sugar, mangosteen peel was added, research on mangosteen peel content was previously conducted by Maligan et al (2018) which shows that the compounds contained in the mangosteen rind extract, besides working as an antioxidant by donating electrons to free radicals, can also work as an inducer which will trigger the expression of the antioxidant coding gene through activation of Nrf2.…”
Section: Figure 2 Graphic Results Of Testing Sugar Levels In Each Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…We find these three herbal ingredients in Indonesia as nutritional and health supplements. Several studies have proven some of these herbal ingredients (cinnamon, aloe vera, and fenugreek seeds) have antidiabetic and hypolipidemic properties because they have high antioxidant content such as flavonoids, saponins, tannins, and alkaloids (Belguith-Hadriche et al, 2013;Kusumaningtyas et al, 2014;Samaneh et al, 2015;Beji et al, 2018). Bioactive components mainly terpenoids, alkaloids, flavonoids, and other types of NPs, which exhibit in vivo hypoglycemic effects (Ma et al, 2022).…”
Section: Introductionmentioning
confidence: 99%